(untitled) (Italian Journal of Public Health, 2009)
Abraham Flexner, in 1910, led an attack on the inadequacy of the medical schools in the United States. In opposition to the traditional clinical type training he proposed a new laboratory centred model, with a strong emphasis on basic sciences. These university lab experiments were one of the main driving forces in the development of medical sciences in the USA. The work of a pedagogue caused a real medical revolution, the outcomes of which were important but not all positive.